Analisis Kinerja Keuangan Sebelum Dan Setelah Jatuhnya Lehman Brothers Pada Perusahaan Asuransi Di Bursa Efek Indonesia - Hartini, Jummaini S (Universitas Malikussaleh, 2013)
The research was conducted to analyze the differences in financial performance before and after the collapse of Lehman Brothers by the ratio of liquidity, solvency, profitability and growth of the insurance companies on the Stock Exchange. The data used in this study are the financial statements of the prior year (2007) the collapse of Lehman Brothers and the year after (2009) the collapse of Lehman Brothers. Hypothesis testing is performed using different test pairs (paired sample t-test) with a significance level = 5% processed constructively program SPSS version 16.0. The test results showed that the value of tcalculate < ttable on the ratio of liquidity, solvency and growth while tcalculate < ttable the profitability ratios. This means that there is no difference in financial performance through liquidity ratios, solvency, and the growth of the insurance companies on the Stock Exchange and there are differences in financial performance with profitability ratios on insurance companies on the Stock Exchange. The average (mean) ratios used in the study for the ratio (current ratio, quick ratio, cash ratio) decreased whereas other ratios (debt ratio, debt to equity ratio, return on investment as, return on equity, earnings per share , the profit margin on sales, and net income growth) has increased.